The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0074-02762002000400021
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation between Seminal and Plasma HIV-1 Viral Loads is Associated with CD4T Cell Depletion in Therapy-naïve HIV-1+ Patients

Abstract: The present study was conducted to investigate a possible correlation between plasma (PVL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…(i) Overall. Similar to previous studies (13,39,56,69,72), we found a positive trend between HIV RNA levels in blood and semen (P ϭ 0.07), while no correlations were found between seminal HIV and CMV levels (P ϭ 0.35) or between seminal HSV and CMV levels (P ϭ 0.39). Activation levels (RA-CD38 ϩ ) of CD4 ϩ and CD8 ϩ subsets in blood were highly correlated with each other (P Ͻ 0.001) and with activation of CD8 ϩ T cells in semen (P Ͻ 0.01).…”
Section: Study Participantssupporting
confidence: 90%
See 1 more Smart Citation
“…(i) Overall. Similar to previous studies (13,39,56,69,72), we found a positive trend between HIV RNA levels in blood and semen (P ϭ 0.07), while no correlations were found between seminal HIV and CMV levels (P ϭ 0.35) or between seminal HSV and CMV levels (P ϭ 0.39). Activation levels (RA-CD38 ϩ ) of CD4 ϩ and CD8 ϩ subsets in blood were highly correlated with each other (P Ͻ 0.001) and with activation of CD8 ϩ T cells in semen (P Ͻ 0.01).…”
Section: Study Participantssupporting
confidence: 90%
“…Although HIV RNA levels in blood roughly correlate with levels in seminal plasma (13,39,56,69,72), local genital factors, particularly concomitant sexually transmitted infections (STI), can increase HIV shedding in semen (38,39,61). Common bacterial STI can also increase the number of immune cells in the genital tract (9,52), and elevated counts of white blood cells in semen are associated with higher seminal HIV shedding (3,4,69,80).…”
mentioning
confidence: 99%
“…Although HIV-1 RNA levels in blood correlate with levels in seminal plasma[3,810], local genital factors, particularly concomitant bacterial sexual transmitted infections (STI), can increase HIV-1 shedding in semen [1012]. Not only bacterial STI but also chronic viral co-infections, e.g.herpes simplex virus type 2 (HSV-2) and cytomegalovirus (CMV),likely influence HIV-1 pathogenesis, transmission and dynamics within the genital tract[1316].…”
Section: Introductionmentioning
confidence: 99%
“…Viral load of HIV measured in blood plasma is known to be related to HIV transmission risk (1,2), but viral loads in semen and in blood plasma may be discordant, and blood viral load cannot precisely reflect the HIV transmission risk (3,4). Semen preparation techniques are helpful for decreasing the viral load in semen (5,6) and frequently are being applied in the settings of medically assisted procreation.…”
mentioning
confidence: 99%